The Relationship Between Emotional Intelligence and Leadership Effectiveness Among Coaches at The XYZ Training Center - Ismail, Fadillah; Mohd Rosli, Nur Amalina; Abdul Kadir, Adibah (Journal of Social Transformation and Regional Development, 2021)
Emotional intelligence plays a very important role for a leader because it can help the effectiveness of coach leadership among trainees and can even guarantee the transfer of training that has been given to trainees. When there is a failure to curb this situation will have a more negative impact on organizations and individuals, and if it is not proactively addressed. Therefore, this study aims to identify the level and relationship between emotional intelligence and leadership effectiveness among coaches. A total of 74 sets of questionnaires were distributed to respondents who have participated in the Transformation Program (Team Building) organized by XYZ training center on October 20, 2018, until October 22, 2018. Descriptive analysis shows the results of the study on emotional intelligence level and leadership effectiveness among coaches. While the correlation analysis proves that there is a significant relationship with r = 0.828 between emotional intelligence and leadership effectiveness among coaches. Thus, this study has shown that emotional intelligence has a significant relationship with leadership effectiveness among coaches.